2018
DOI: 10.1371/journal.pone.0203902
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac leptin overexpression in the context of acute MI and reperfusion potentiates myocardial remodeling and left ventricular dysfunction

Abstract: BackgroundAcute MI induces leptin expression in the heart, however the role of myocardial leptin in cardiac ischemia and reperfusion (IR) remains unknown. To shed light on the effects of elevated levels of leptin in the myocardium, we overexpressed cardiac leptin and assessed local remodeling and myocardial function in this context.Methods and resultsCardiac leptin overexpression was stimulated in mice undergoing IR by a single intraperitoneal injection of leptin antagonist (LepA). All mice exhibited a normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 41 publications
0
18
0
1
Order By: Relevance
“…Plasma concentration of leptin corresponds mainly to its synthesis by adipocytes. Recent study on murine model suggests that the hypertrophic action is related to the overexpression of cardiac leptin [ 26 ]. The limitations of available measurement methods make it impossible to determine the concentration of cardiac leptin in samples from patients.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma concentration of leptin corresponds mainly to its synthesis by adipocytes. Recent study on murine model suggests that the hypertrophic action is related to the overexpression of cardiac leptin [ 26 ]. The limitations of available measurement methods make it impossible to determine the concentration of cardiac leptin in samples from patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperleptinemia is considered an independent risk factor for coronary artery disease (CAD) and a strong predictor of acute myocardial infarction (AMI) [ 47 , 48 ]. In mice with leptin overexpression, cardiac ischemia/reperfusion (I/R) leads to cardiomyocyte hypertrophy and fibrosis and worsens myocardial dysfunction [ 49 ]. Patients with myocardial infarction (MI) have increased circulating levels of leptin, which correlates with pro-inflammatory markers, suggesting that leptin is associated with the inflammatory response produced during an AMI [ 50 , 51 , 52 ].…”
Section: Role Of Some Adipokines In Inflammatory Processes Associamentioning
confidence: 99%
“…164 Therefore, it has autocrine and paracrine effects on the vascular modulation process. 36 Investigations done on animal models showed that leptin leads to the development of atherosclerosis and thrombosis, which act as risk factors for CAD. 27 Even though animal investigations revealed that it contributes to atherosclerosis development, 115 findings from clinical investigations as well as experimental animal studies showed leptin's protective effect against atherosclerosis.…”
Section: Hyperleptinemia Aggravates Further Cardiovascular Risk Complicationmentioning
confidence: 99%
“…34 Even if contradictory data has been shown in vascular diseases, 35 hyperleptinemia is the adverse effect of cardiovascular complications such as stroke, heart failure, and acute myocardial infarction. 36 Although scientific evidence had argument on leptin effect in coronary artery disease, it has a correlation with intimamedia thickness and calcification of coronary artery among type II diabetes mellitus patients. 37 Coronary artery disease (CAD) is associated with increased synthesis of the perivascular adipose tissue derived leptin and its atherogenic effect.…”
Section: Introductionmentioning
confidence: 99%